A G-triplex luminescent switch-on probe for the detection of mung bean nuclease activity. Issue 3 (3rd December 2014) - Ma, Dik-Lung; Lu, Lihua; Lin, Sheng; He, Bingyong; Leung, Chung-Hang
Abstract : A G-triplex luminescent switch-on probe for the detection of nuclease activity. Abstract : A cyclometallated Ir(iii ) complex was synthesised and evaluated for the ability to act as a luminescent G-triplex probe. The iridium(iii ) complex1 [Ir(phq)2 (2, 9-dmphen)]PF6 (where phq = 2-phenylquinoline; 2, 9-dmphen = 2, 9-dimethyl-1, 10-phenanthroline) exhibited high luminescence for G-triplex DNA over dsDNA and ssDNA, and was employed to construct a label-free G-triplex-based assay for mung bean nuclease activity in aqueous solution. This method was highly sensitive and selective for MB nuclease activity over other DNA-modifying enzymes.